2017
DOI: 10.1002/rcm.7954
|View full text |Cite
|
Sign up to set email alerts
|

Post‐mortem oxygen isotope exchange within cultured diatom silica

Abstract: RationalePotential post‐mortem alteration to the oxygen isotope composition of biogenic silica is critical to the validity of palaeoclimate reconstructions based on oxygen isotope ratios (δ18O values) from sedimentary silica. We calculate the degree of oxygen isotope alteration within freshly cultured diatom biogenic silica in response to heating and storing in the laboratory.MethodsThe experiments used freshly cultured diatom silica. Silica samples were either stored in water or dried at temperatures between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 53 publications
3
16
0
Order By: Relevance
“…Our goal of defining a frustule temperature effect is clearly predicated on the degree to which we successfully isolated and measured only the structural oxygen fraction. Furthermore, we must confirm that the structural oxygen isotope composition is not being reset during chemical treatment prior to fluorination, as was observed in previous experimental work (Tyler et al 2017). In that study, Tyler et al (2017) heated two diatom samples in water of distinct isotopic composition and estimated that, even after stepwise fluorination, samples heated at 80°C are 40% re‐equilibrated after 1 week (Tyler et al 2017).…”
Section: Methodssupporting
confidence: 75%
See 1 more Smart Citation
“…Our goal of defining a frustule temperature effect is clearly predicated on the degree to which we successfully isolated and measured only the structural oxygen fraction. Furthermore, we must confirm that the structural oxygen isotope composition is not being reset during chemical treatment prior to fluorination, as was observed in previous experimental work (Tyler et al 2017). In that study, Tyler et al (2017) heated two diatom samples in water of distinct isotopic composition and estimated that, even after stepwise fluorination, samples heated at 80°C are 40% re‐equilibrated after 1 week (Tyler et al 2017).…”
Section: Methodssupporting
confidence: 75%
“…The lab water used during the chemical pretreatment has a δ 18 O composition of −6.8‰. The low δ 18 O oxygen generated in early prefluorination steps therefore shows the contribution of adsorbed water and exchangeable hydroxyl oxygen, which may have re‐equilibrated at high‐temperature with lab water during chemical pretreatment (Li et al 2015; Tyler et al 2017). This reactive oxygen is consumed during prefluorination; both diatom species ultimately approach a steady state or “final” δ 18 O value before the samples were laser fluorinated.…”
Section: Methodsmentioning
confidence: 99%
“…In a pioneering study, Schmidt et al (1997) suggested that there is no regular correlation between temperature and the oxygen isotope fractionation between modern diatoms and the water in which they biomineralise. This led to the hypothesis that the temperature-dependent oxygen isotope fractionation preserved in biogenic opaline sediments may, in some environments, have been established during diagenesis (see below) rather than acquired during growth, a subject open to recent investigation (Menicucci et al 2017;Tyler et al 2017).…”
Section: Interpreting Stable Oxygen and Silicon Isotopes Of Diatom Opalmentioning
confidence: 99%
“…These oxygen-bearing compounds (-OH and H 2 O) can exchange freely with their environmental lake water (Fig. 3), for example with sedimentary pore water during the burial of diatoms (Mopper and Garlick 1971;Kawabe 1978;Mikkelsen et al 1978;Schmidt et al 1997;Brandriss et al 1998;Moschen et al 2006) or with laboratory water used in diatom cleaning preparation techniques (Tyler et al 2017). The hydrous layer must be removed prior to d 18 O measurements due to its ready exchangeability (most notable in modern diatoms), which makes it a complex mineral to analyse (Leng and Sloane 2008).…”
Section: The Hydrous Layer and Maturation Of Oxygen Isotopes In Biogementioning
confidence: 99%
“…The Garba Guracha δ 18 O diatom record δ 18 O lake water and temperature at the time of frustule formation define the δ 18 O diatom composition of aquatic diatoms (Labeyrie, 1974;Leclerc and Labeyrie, 1987;Leng and Barker, 2006). Some processes in the incorporation of oxygen isotopes into diatom silica (summarized by Bird et al, 2020) still require a better understanding, such as (1) species-specific fractionation (Bailey et al, 2014), (2) post-mortem alteration of the oxygen isotopic composition (Tyler et al, 2017), and (3) the effect of diagenesis on oxygen isotope fractionation and exchange (Dodd et al, 2012). However, δ 18 O diatom analyses have been applied successfully to many archives as a proxy for P/E to identify wet and dry conditions (Polissar et al, 2006;Meyer et al, 2015), moisture source (Rosqvist et al, 2004;Leng et al, 2005;Schiff et al, 2009), δ 18 O precipitation (Morley et al, 2005;Mackay et al, 2013;Bailey et al, 2015), hydrological changes (Narancic et al, 2016;Kostrova et al, 2019), and temperature (Kostrova et al, 2014).…”
Section: Discussionmentioning
confidence: 99%